Designed miniaturization of microfluidic biosensor platforms using the stop-flow technique. Issue 21 (5th September 2016) - Dincer, C.; Kling, A.; Chatelle, C.; Armbrecht, L.; Kieninger, J.; Weber, W.; Urban, G. A.
Abstract : Here, we present a novel approach to increase the degree of miniaturization as well as the sensitivity of biosensor platforms by the optimization of microfluidic stop-flow techniques independent of the applied detection technique ( e.g. electrochemical or optical). Abstract : Here, we present a novel approach to increase the degree of miniaturization as well as the sensitivity of biosensor platforms by the optimization of microfluidic stop-flow techniques independent of the applied detection technique ( e.g. electrochemical or optical). The readout of the labeled bioassays, immobilized in a microfluidic channel, under stop-flow conditions leads to a rectangular shaped peak signal. Data evaluation using the peak height allows for a high level miniaturization of the channel geometries. To study the main advantages and limitations of this method by numerical simulations, a universally applicable model system is introduced for the first time. Consequently, proof-of-principle experiments were successfully performed with standard and miniaturized versions of an electrochemical biosensor platform utilizing a repressor protein-based assay for tetracycline antibiotics. Herein, the measured current peak heights are the same despite the sextuple reduction of the channel dimensions. Thus, this results in a 22-fold signal amplification compared to the constant flow measurements in the case of the miniaturized version.